36-2(6-2x)=-16

Simple and best practice solution for 36-2(6-2x)=-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36-2(6-2x)=-16 equation:


Simplifying
36 + -2(6 + -2x) = -16
36 + (6 * -2 + -2x * -2) = -16
36 + (-12 + 4x) = -16

Combine like terms: 36 + -12 = 24
24 + 4x = -16

Solving
24 + 4x = -16

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + 4x = -16 + -24

Combine like terms: 24 + -24 = 0
0 + 4x = -16 + -24
4x = -16 + -24

Combine like terms: -16 + -24 = -40
4x = -40

Divide each side by '4'.
x = -10

Simplifying
x = -10

See similar equations:

| n+15=3l | | n/11=40/55 | | 4(20x+15)=1180 | | 4t+7-1=19 | | 8(-9)-(-17)= | | -5=x-2 | | .07*(6000-x)=360 | | 9+4x-2=-15 | | X-1-31=4 | | 3(2x+5)-6(x+2)= | | -2m+13=2-3 | | 15+7(2-4x)=-35 | | 4x+14=60 | | .07*(10000-x)=900 | | r=1979+-40x | | 7+4x=3(2+x) | | 2(6+8*7)6(7+9-9)=9 | | 54=3t | | 3a-5=da | | 7-2q=3 | | -3(x-4)=48 | | -7+3x+5x=-71 | | -2(2f-4)=g(h-3) | | 21-5(7+5x)=-15 | | ax-m=6 | | 2(v-4)-10=-2(-1+4v) | | 18x-5=3(x-2) | | q+2.7=-.9 | | 2c=1000-10+100 | | -5x(-6x-x)=6+3(8+2x) | | 7x-220=4x+80 | | 7.2x-3.8=2.2x+4 |

Equations solver categories